METHODS OF TEACHING AND TRAINING FUTURE DOCTORS AT THE DEPARTMENT OF INTERNAL MEDICINE - Гончарук, Л.М.; Піддубна, А.А.; Криган, А.; Хомич, М. (SWorldJournal, 2023)
The article highlights the main priorities of the development of modern medical education. The greatest attention is paid to the quality training of doctors through the use of the latest innovative technologies in the educational process. Methods of teac